2021
DOI: 10.1186/s12935-021-02085-6
|View full text |Cite
|
Sign up to set email alerts
|

Tumor microenvironment: a prospective target of natural alkaloids for cancer treatment

Abstract: Malignant tumor has become one of the major diseases that seriously endangers human health. Numerous studies have demonstrated that tumor microenvironment (TME) is closely associated with patient prognosis. Tumor growth and progression are strongly dependent on its surrounding tumor microenvironment, because the optimal conditions originated from stromal elements are required for cancer cell proliferation, invasion, metastasis and drug resistance. The tumor microenvironment is an environment rich in immune/inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 200 publications
(263 reference statements)
0
8
0
Order By: Relevance
“…Conversely, the overt anti-inflammatory activity of OMT revealed an inhibitory effect on p-JAK2, p-STAT3, and TGF-β1 [ 46 ]. OMT was found to downregulate JAK2 and STAT3 phosphorylation in multiple pathophysiological states [ 47 , 48 ]. Thus, the JAK2/STAT3 pathway may be considered to be of vital importance in ameliorating the effects of OMT against diabetic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the overt anti-inflammatory activity of OMT revealed an inhibitory effect on p-JAK2, p-STAT3, and TGF-β1 [ 46 ]. OMT was found to downregulate JAK2 and STAT3 phosphorylation in multiple pathophysiological states [ 47 , 48 ]. Thus, the JAK2/STAT3 pathway may be considered to be of vital importance in ameliorating the effects of OMT against diabetic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…As for TME and tumor-infiltrating immune cells, tumors were confronted with a complex TME, mainly consisting of cancer cells, stromal cells, tumor-infiltrating immune cells, extracellular matrix, or blood vessels [29]. A growing number of research sug-gested that TME and tumor-infiltrating immune cells could predict the prognosis and the therapeutic responses of chemotherapy or immunotherapy for multiple cancers [30][31][32]. Our results found that 17 out of 22 tumor-infiltrating immune cells by "CIBERSORT", 27 out of 28 immune cell scores by "ssGSEA", nine of 10 immune cell scores by "MCP-counter", ESTIMATEScore, stromalScore, and immuneScore by "ESTIMATE", were all differently expressed in three ccRCC metabolic subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Natural alkaloids are regarded as valuable sources of anti-cancer medicines because they not only exhibit potent anti-tumor effects when taken alone but also when combined with other anti-tumor agents ( Luo et al, 2021 ). Consequently, alkaloids have attracted considerable interest for tumor treatment.…”
Section: Intervention Of Natural Products On the Canonical Wnt Pathwa...mentioning
confidence: 99%